Evaluación de la simetría de la tiroides bovina mediante técnicas de morfometría geométrica - Parés-Casanova, P. M. (2024)
Fifteen glands from clinically healthy bovine calves were evaluated using geometric morphometry methods. The right and left lobes were studied separately, comparing their differences in size and shape. The results reflected the presence of fluctuating asymmetry for the shape; that is, a deviation from the symmetry between lobes expected for this bilateral structure. No directional asymmetry was found. It is assumed that the degree of asymmetry is completely physiological; That is, fluctuating asymmetry, commonly used as a measure of developmental instability, would not represent in the case studied an inability of the gland to maintain its normal physiology.